Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan PT. Prima Sola Indonesia Sidoarjo - Lukya Salmi Maryamis; Iswati Iswati; Anis Fitriyasari; Arief Widijatmoko (Global Leadership Organizational Research in Management, 2024)
Compensation is a method adopted by companies as part of their strategy to encourage increased employee performance and motivation. Incentive systems are used in awards to reward individual work results. It is not only rewards that the company must give to its employees, it is also important to provide motivational encouragement to the company so that each team member in it can achieve optimal performance. The method applied in this research is quantitative research. Data is collected through research instruments and analyzed numerically or statistically. In this quantitative research, there are two types of variables that have been identified, namely independent variables such as compensation (X1) and motivation (X2), as well as dependent variables which include employee performance (Y). The test results show that (1) Variable X1, namely termination, has a positive and significant effect on employee performance at PT. Prima Sola Indonesia. This can be seen from the significant value which is smaller than 0.05. (2) Variable X2, namely Motivation, has a positive and significant effect on Employee Performance at PT. Prima Sola Indonesia. This can be seen from the significant value which is smaller than 0.05. (3) Variables X1 (Compensation) and X2 (Motivation) have a positive and significant impact simultaneously on Employee Performance.